(untitled) (Precision Medicine Communications, 2022)
Precision medicine focuses on understanding the heterogeneity of cancer at the individual patient level. Cancer may develop from multiple genetic mutations, and each cancer cell might have its own genetic makeup. The individualized features of cancer contribute to the challenge of developing an effective chemotherapy regimen. The advances in synthetic biology and single-cell RNA sequencing technologies have made it possible to longitudinally track the dynamic changes of gene expression in cancer cells during chemotherapy. This understanding can be translated into developing individualized chemotherapy regimens. Precision medicine can be used to monitor the efficacy of chemotherapy and predict the likelihood of chemoresistance. Currently, the response of cancer to chemotherapy is mostly assessed through a single-endpoint measurement using imaging technologies such as computed tomography. This approach is limited because it is not sensitive to tumor dormancy and cancer heterogeneity. The recent advances in high-throughput sequencing technologies now enable the detection of residual cancer cells and tumor dormancy. This information can be used to monitor the efficacy of chemotherapy and predict the likelihood of chemoresistance. Precision medicine can be used to identify genetic variations that may influence how a patient will respond to a particular drug. The information so obtained can then be used to help the healthcare provider choose the most appropriate chemotherapy regimen for each patient. In addition, precision medicine can be used to predict which patients may be more likely to experience serious side effects from chemotherapy, and can help to guide preventive strategies, such as dose adjustments or pre-treatment with other medications. Although precision medicine is increasingly being used to help tailor cancer chemotherapy to the individual patient to maximize the efficacy of the treatment and minimize side effects, it holds great promise in cancer chemotherapy only when backed by strong evidence. To fully realize the potential of precision medicine, it is important to consider the following issues. First, precision medicine approaches need to be integrated into clinical decision-making. Second, there is a need to develop robust and reliable biomarkers for precision medicine. Third, it is important to develop a comprehensive understanding of the heterogeneity of cancer. Fourth, it is necessary to develop efficient computational methods for analyzing high-throughput sequencing data. Finally, it is important to establish a robust infrastructure for storing and sharing precision medicine data Sami Siraj Editor-In-Chief Precision Medicine Communications